2021
DOI: 10.1007/s11845-020-02476-0
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture care during Covid-19: a regional trauma centre’s experience

Abstract: Introduction The Covid-19 pandemic has caused worldwide upheaval from early 2020. Trauma and orthopaedic services are no different. A fundamentally important and significant portion of trauma services is the treatment of fragility fractures of the proximal femur, otherwise known as hip fractures. The hip fracture "Blue book Standards", the key performance indicators (KPIs) associated with appropriate hip fracture care are challenging during non-crisis times. We aim to review Blue Book compliance during the Cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…Preliminary studies from various countries have noted increased mortality with hip fracture cases during this pandemic when compared to similar study cohorts in prior years. [19][20][21][22][23][24][25][26][27] The shortage of personal protective equipment (PPE), reduced OR availability, lack of familiarity with the evolving COVID-19 protocols, visitor restrictions, and reduced physical and occupational therapy potentially negatively impacted the treatment of hip fracture patients.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies from various countries have noted increased mortality with hip fracture cases during this pandemic when compared to similar study cohorts in prior years. [19][20][21][22][23][24][25][26][27] The shortage of personal protective equipment (PPE), reduced OR availability, lack of familiarity with the evolving COVID-19 protocols, visitor restrictions, and reduced physical and occupational therapy potentially negatively impacted the treatment of hip fracture patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] However, HF is still a major burden, one study showed that HFs were the most common type of OF in the epidemic patient group, accounting for 68.4%, followed by thoracolumbar VF (17.0%) and similar observations have been made internationally. [ 10 , 17 ] Moreover the combination of osteoporotic HF and COVID-19 is associated with very poor outcomes. A positive COVID-19 test was associated with a significantly increased risk of 30-day mortality (from 8.5% in April 2019 to 18.2% in April 2020) and even upto 80% for those patients who test positive for COVID-19 as an inpatient.…”
Section: Trend Of Osteoporotic Fracture In Covid-19 Pandemicmentioning
confidence: 64%
“…[ 10 ] This does appear to be consistent with other jurisdictions, which have noted a 32% reduction in trauma presentations during the COVID-19 pandemic. [ 17 ] However, HF is still a major burden, one study showed that HFs were the most common type of OF in the epidemic patient group, accounting for 68.4%, followed by thoracolumbar VF (17.0%) and similar observations have been made internationally. [ 10 , 17 ] Moreover the combination of osteoporotic HF and COVID-19 is associated with very poor outcomes.…”
Section: Trend Of Osteoporotic Fracture In Covid-19 Pandemicmentioning
confidence: 66%
See 1 more Smart Citation
“…Patients with multiple comorbidities scheduled for elective TJA may be at higher risk of succumbing if infected with COVID-19 perioperatively and may also require inpatient recovery in rehabilitation units or nursing homes, further increasing the risk of transmission [16]. With a demonstrated higher complication rate in COVID-19positive patients undergoing hip fracture management, these studies highlight the importance of avoiding contraction during the perioperative period of the elective orthopedic surgery [19,20].…”
mentioning
confidence: 99%